2014
DOI: 10.1002/jcla.21661
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-Modified Albumin May be a Novel Marker for the Diagnosis and Follow-up of Necrotizing Enterocolitis

Abstract: Ischemia-modified albumin was found to be superior to CRP and IL-6 in both diagnosis and follow-up of NEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 27 publications
(56 reference statements)
2
29
0
6
Order By: Relevance
“…This situation can be explained in two ways. First, IMA levels might have increased as a result of hypoxia occurring in tissues after intestinal microvascular ischemia, which is held responsible for the classical clinic of IBD . Second and most likely cause may be due to high levels of oxidative stress and chronic inflammation in patients with IBD compared with the control group .…”
Section: Discussionmentioning
confidence: 92%
“…This situation can be explained in two ways. First, IMA levels might have increased as a result of hypoxia occurring in tissues after intestinal microvascular ischemia, which is held responsible for the classical clinic of IBD . Second and most likely cause may be due to high levels of oxidative stress and chronic inflammation in patients with IBD compared with the control group .…”
Section: Discussionmentioning
confidence: 92%
“…Yakut et al [13] have reported that IMA levels are sensitive and effective marker for diagnosing NEC in close association with intestinal hypoxia, monitoring and decision-making for surgery in preterm infants. Kumral et al [12] have stated that asphyxia in low birth weight infants exists more than term infants, and this situation increases reactive oxygen species [21].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, few studies have determined that cord blood levels of IMA are higher in perinatal asfixia and complicated deliveries thought to be associated with fetal distress, hypoxia and oxidative stress in newborns. Additionally, some clinical and experimental studies have recently indicated elevated levels of IMA in ischemic and hypoxic conditions such as necrotizing enterocolitis (NEC) in newborns [10][11][12][13]. In these considerations, the primary aim of this study was to evaluate the diagnostic significance of serum IMA level in newborns with RDS which is a leading cause of hypoxia particularly in preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…16 İnflamasyona ve reaktif oksijen radikalleri (ROS) üreti-mine bağlı olarak oluşan iskemik olaylarda, serumda ölçülebilen IMA seviyeleri artan CRP ve IL-6 seviyeleri ile anlamlı derecede ilişkili bulunmuştur. 16 Nekrotizan periodontal hastalıklarda IMA seviyelerini inceleyen bir çalışma literatürde bulunmamaktadır. Yine literatürde NUP hastalarının serum CRP ve IL-6 seviyelerini değerlendiren bir çalışma yoktur.…”
Section: Gġrġġunclassified
“…[23][24][25] Hipoksi ve iskeminin, pro-inflamatuar prosesi indükle-diği bunun sonucunda nötrofillerin aktive olarak bir çok sitokini ve reaktif oksijen türünü ürettiği ve bu ürün-lerin hipoksi ve iskemide önemli patojenik mediatörler olduğu bilinmektedir. 16 IL-6, mononükleer fagositlerden salınan pro-inflamatuar bir sitokindir ve nötrofil aktivasyonu sonucunda sistemik inflamatuar bir cevap oluşturur. 26 Deneysel bir akut mezenterik iskemi modelinde, serum IMA seviyeleri ve IL-6 arasında pozitif bir korelasyon gösterilmiştir.…”
Section: Tartiġmaunclassified